Organocatalytic Asymmetric X–H Insertion Reactions of α-Carbonyl Sulfonium Ylides, Sulfoxonium Ylides, and Sulfonium Salts - Hu, Ruifeng; Miao, Chun-Bao; Guo, Wengang; Sun, Jianwei (Synlett, 2025)
Since their initial discovery by Ingold and Jessop in 1930, sulfur ylides have been recognized as a highly versatile class of compounds in organic synthesis. Their reactivity, which closely resembles that of diazo compounds, has enabled them to serve as valuable surrogates for safe and stable carbene precursors, offering unique advantages in large-scale syntheses. However, compared to diazo compounds, the catalytic asymmetric reactions involving sulfur ylides, whether as substrates or intermediates, remain relatively underexplored. In this account, we mainly summarize our recent advancements in this area, focusing particularly on their applications in organocatalytic asymmetric X–H (X = N, N3, Cl, and C) insertion reactions. These reactions typically involve enantio-determining and rate-determining C–X bond formation in combination with dynamic kinetic resolution, thus leading to both high chemical efficiency and enantiocontrol.1 Introduction2 S–H Insertion Reactions of Sulfoxonium Ylides3 N–H Insertion Reactions of Sulfonium Ylides4 N–H Insertion Reactions of Sulfoxonium Ylides5 One-Pot Sequential Ylide Formation and N–H insertion Reactions6 N3–H Insertion Reactions of Sulfoxonium Ylides7 Chlorination of Sulfonium Salts8 C–H Insertion Reactions of Sulfoxonium Ylides9 Conclusion and Outlook
Keywords: organocatalysis; enantioselectivity; α-carbonyl; sulfonium ylide; sulfoxonium ylide; sulfonium salt; N–H insertion